PROFESSIONAL COMPETENCIES OF MODERN LIBRARY SPECIALIST - Kostyrko, Tamara M. (University Library at a New Stage of Social Communications Development. Conference Proceedings, 2019)
Short overview of international approaches to the definition and use of competencies, competency structure, the use of a competency model considered. Conclusions of the necessity of qualitative changes in professional competence improving, targeted training programs are done.